Assessing the Role of Environmental Expenditures and Green Transport in Emissions Released by Transport: An Application of ARDL Approach - Hussain, Zahid; Miao, Cuifen; Zhang, Weitu; Khan, Muhammad Kaleem; Xia, Zhiqing (Frontiers in Environmental Science, 2021)
This study investigates the effects of transport and environmental factors on transport carbon dioxide emissions (TCO2). It employs cross-sectional autoregressive distributed lags for the estimation in the short and long runs and examines the panel time-series data from 2000 to 2020 in the OECD countries. This method allows heterogeneity in the dependencies and slope parameters across the countries. The results demonstrate that road and railway traffic movements increase the amount of TCO2 in the short and long runs. In addition, transport energy consumption is the driving factor in releasing TCO2 in the long run. Moreover, the joint effect of locomotives and transport energy consumption significantly reduces TCO2 in the short run. By contrast, the findings support the argument that environmental expenditures and green transport mitigate TCO2 in the long run. The findings also show an inverted u-shaped relationship between TCO2 and transport energy consumption. With the empirical findings as a basis, we suggest that the OECD countries should reduce traffic movements and enhance the environmental expenditures so that they may produce green transport vehicles to combat environmental issues.